2015
DOI: 10.1007/s00256-015-2308-0
|View full text |Cite
|
Sign up to set email alerts
|

Scapholunate kinematics of asymptomatic wrists in comparison with symptomatic contralateral wrists using four-dimensional CT examinations: initial clinical experience

Abstract: In patients with wrist pain suspicious for SLIL injury and inconclusive radiographs, SL interval increase can be detected with 4DCT in the symptomatic wrist compared to the asymptomatic wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Dynamic CT has been used for the evaluation of in vivo carpal motion, but most studies were based on subjective motion description and manual punctual measurements (16,18,28). In our study, the in vivo variation of RSA and LCA in normal wrists was measured in all time points of radioulnar deviation motion cycle with a semiautomatic postprocessing and a low-dose acquisition protocol (effective dose of ,0.02 mSv).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic CT has been used for the evaluation of in vivo carpal motion, but most studies were based on subjective motion description and manual punctual measurements (16,18,28). In our study, the in vivo variation of RSA and LCA in normal wrists was measured in all time points of radioulnar deviation motion cycle with a semiautomatic postprocessing and a low-dose acquisition protocol (effective dose of ,0.02 mSv).…”
Section: Discussionmentioning
confidence: 99%
“…Four-dimensional (4D) CT with wide-area detectors allows a kinematic assessment of active wrist motion depicting slight positional bone changes with high temporal and spatial resolution. This technique has shown potential for the evaluation of carpal instability, particularly in cases of inconclusive initial assessment (14)(15)(16)(17)(18). Recently, commercially available postprocessing tools allowing semiautomatic quantitative angular measurement with 4D CT joint studies became available for clinical use (19)(20)(21).…”
mentioning
confidence: 99%
“…Research to date has demonstrated the feasibility of 4D CT for use in imaging upper limb joints and for the diagnosis and surgical planning of costoclavicular impingement, scapholunate instability, capitate subluxation, pisotriquetral instability, acromioclavicular dislocation, and snapping scapula. [10][11][12][13][14] The technique has also been shown to produce images with high spatial and temporal resolution. 15,16…”
mentioning
confidence: 99%
“…Multiple different maneuvers can be performed with a single bolus of contrast. 79 KCT with or without arthrography can be used to assess intra-articular ligaments under stress, for example in the assessment of carpal instability, 83 and it can also be used to evaluate surgical outcomes after carpal ligament repair. 81 KCT may have a role in the evaluation of joint stability, assessment of the integrity of intra-articular ligaments, and in bony tracking abnormalities.…”
Section: Kinematic Ctmentioning
confidence: 99%